Intensive BP Control and eGFR Declines: Are These Events Due to Hemodynamic Effects and Are Changes Reversible? - Chen, Debbie C.; McCallum, Wendy; Sarnak, Mark J.; Ku, Elaine (Current cardiology reports, 2020)
Purpose of Review Acute declines in estimated glomerular filtration rate (eGFR) are often observed during intensive blood pressure (BP) lowering. This review focuses on identifying the various mechanisms of eGFR decline associated with intensive BP lowering and evaluates the evidence linking BP control with kidney and cardiovascular (CV) outcomes. Recent Findings In 2017, the American College of Cardiology and the American Heart Association (ACC/AHA) began recommending treatment of all individuals to a BP target of < 130/80 mmHg. Since then, multiple post hoc analyses of BP trials have associated intensive BP lowering with acute declines in kidney function and acute kidney injury; whether these represent reversible changes in the kidney is still debated. Summary There is ample evidence that intensive BP lowering is associated with declines in eGFR. The clinical implications of these events remain unclear. Individualizing the risks and benefits of intensive BP therapy continues to be warranted.